Water Shortage Strongly Alters Formation of Calcium Oxalate Druse Crystals and Leaf Traits in Fagopyrum esculentum - Alenka Gaberščik; Mateja Grašič; Katarina Vogel-Mikuš; Mateja Germ; Aleksandra Golob (Plants, 2020)
Common buckwheat (Fagopyrum esculentum Moench) is a robust plant with high resistance to different environmental constraints. It contains high levels of calcium oxalate (CaOx) druse crystals, although their role remains obscure. The objective was to examine the effects of water shortage on plant biomass partition and leaf traits and formation of CaOx druse crystals in common buckwheat. Buckwheat plants were exposed to favorable and reduced water availability for 28 days. The element composition and morphological, biochemical, physiological and optical traits of the leaves, and the plant biomass were investigated under these conditions. Measurements of photochemical efficiency of photosystem II showed undisturbed functioning for buckwheat exposed to water shortage, apparently due to partially closed stomata and more efficient water regulation. Strong relationships were seen between water-related parameters and Ca, Mn and S content, and size and density of CaOx druse crystals. Redundancy analysis revealed the importance of the size of CaOx druse crystals to explain reflection in the UV range. Water shortage resulted in shorter plants with the same leaf mass (i.e., increased mass:height ratio), which, together with denser leaf tissue and higher content of photosynthetic pigments and protective substances, provides an advantage under extreme weather conditions.